Monitoring and Evaluation the Urban Growth Pattern in Weh Island, Indonesia - Faisal Azwar; Ashfa Achmad; Mahidin; Mirza Irwansyah (International Journal of Architecture and Urbanism, 2026)
Urban growth has become a global issue in building an environment impacting life and the environment. Cities continue to grow, including cities on small islands such as the city in Weh Island in Aceh Province, Indonesia. Considering its strategic location as the outermost island and its natural potential, the city in Weh Island may become the center of national strategic activities in Indonesia's national urban system. It is mainly driven by disorganized expansion, increasing immigration, and rapid population growth. In this context, land use and land cover (LULC) changes are considered one of the main components of sustainable urban growth's monitoring and evaluation strategy. Remote sensing methodology and geospatial technology can analyze the detection of land use/cover changes. This paper attempted to assess land use and the detection of its changes by using the Geographic Information System (GIS) in Weh Island from 2010 to 2020. An analysis of land use changes showed that the Built-up Area had increased from 489.06 ha to 736.92 ha (50.68%). Meanwhile, woodland had decreased from 6,071.22 ha to 5,452.92 ha (10.18%). However, Weh Island's most comprehensive land cover remained woodland at 50% in 2010 and 45% in 2020. The second largest land cover was agriculture areas at 34% in 2010 and 36% in 2020. Information on urban growth, land use studies, and land cover changes are beneficial for local governments and city planners to improve plans for sustainable urban development.